Menstrual hygiene practices in context of schooling: A community study among rural adolescent girls in Varanasi - Sangeeta Kansal; Sweta Singh; Alok Kumar (Wolters Kluwer Medknow Publications, 2016)
Introduction: Up until now, poor menstrual hygiene in developing countries has been an insufficiently acknowledged problem. The lack of attention to this issue is striking as we cannot achieve several Millennium Development Goals (MDGs), that is, 2, 3 4,5, and5B. This study aimed to assess the level of awareness about menarche and hygienic practices during menstruation in context of schooling . Materials and Methods: Community-based cross-sectional study using a mix method approach (qualitative and quantitative). It was conducted among 650 adolescent girls in the field practice area of Rural Health and Training Centre, Chiraigaon block of district Varanasi between January and June2011. Pretested, semistructured interview schedule was used. Data were analyzed statistically by using Statistical Package for Social Sciences (SPSS) software. Results: Out of the total 650 respondents, 590 (90.78%) had attained menarche at the time of interview and only one-third of the respondents (29.4%) were aware of menstruation before menarche and sisters (55%) played the key role in providing information to them. Only 31% respondents were using sanitary pads during menstruation. Self-reported reproductive tract infection (RTI) was observed more in respondents not maintaining hygienic practices (6.6%) as compared to those maintaining hygiene (2.6%). Conclusion and Recommendations: From the Focus Group Discussions (FGDs) as well as quantitative survey it was observed that the awareness about menarche before its onset was still poor in rural areas. Significant association (P < 0.05) was observed between respondent education and their awareness about menarche before its onset. Therefore, it is recommended that teachers can play an influential role in informing them about changes during adolescence, especially about menarche and other issues related to menstruation. As per the present study, sisters and mothers were the major source of information. Therefore, there is a need for the provision of comprehensive family life education for the parents also.